AGROWISATA JAMUR TIRAM BERBASIS EKONOMI KREATIF: STUDI KASUS DI KAWASAN BOROBUDUR - Setyoko, Puput; Mistriani, Nina (Kepariwisataan: Jurnal Ilmiah, 2025)
AbstractThis study aims to explore the development of oyster mushroom agro tourism in the Borobudur area as an educational tourism model based on the creative economy. Using a qualitative case study approach, the research examines the transformation of small scale oyster mushroom cultivation into a tourist attraction that fosters local economic empowerment. Data were collected through semi structured interviews, participatory observations, and document analysis, and then analyzed thematically. The findings reveal that oyster mushroom agro tourism enhances farmer's income through product diversification and tourism activities, strengthens local food security, and generates positive social impacts for surrounding communities. The success of this model is supported by innovations in cultivation and product processing, integration with Borobudur tourism packages, as well as institutional support and training programs. A cost benefit analysis demonstrates economic feasibility, with a benefit cost ratio of 2.4 and a payback period of 3.5 years. The study also emphasizes the importance of spatial planning to ensure business sustainability. These findings contribute conceptually to the development of agriculture based and creative economy oriented destinations and provide valuable insights for formulating strategic policies in the tourism and integrated agriculture sectors.Keywords: Agrotourism; Creative Economy; Educational Tourism; Community Empowerment; SustainabilityAbstrakPenelitian ini bertujuan mengeksplorasi pengembangan agrowisata jamur tiram di kawasan Borobudur sebagai model wisata edukatif berbasis ekonomi kreatif. Dengan pendekatan studi kasus kualitatif, kajian menelaah transformasi budidaya jamur tiram skala kecil menjadi atraksi wisata yang mampu mendorong pemberdayaan ekonomi lokal. Data dikumpulkan melalui wawancara semi-terstruktur, observasi partisipatif, dan studi dokumentasi, kemudian dianalisis secara tematik. Hasil penelitian menunjukkan bahwa agrowisata jamur tiram dapat meningkatkan pendapatan petani melalui diversifikasi produk dan aktivitas wisata, memperkuat ketahanan pangan, serta memberikan dampak sosial positif bagi masyarakat sekitar. Keberhasilan model ini ditopang oleh inovasi dalam budidaya dan pengolahan, integrasi dengan paket wisata Borobudur, serta dukungan kelembagaan dan program pelatihan. Analisis biaya-manfaat memperlihatkan kelayakan usaha dengan rasio 2,4 dan periode pengembalian investasi 3,5 tahun. Penelitian juga menekankan pentingnya perencanaan spasial untuk mendukung keberlanjutan. Temuan ini berkontribusi pada pengembangan konsep destinasi berbasis pertanian dan ekonomi kreatif, sekaligus menjadi rujukan dalam penyusunan kebijakan strategis sektor pariwisata dan pertanian terpadu.Kata Kunci: Agrowisata; Ekonomi Kreatif; Wisata Edukasi; Pemberdayaan Masyarakat; Keberlanjutan